Visual and Verbal Communications: Similarities and Differences - Kacharava, Khatuna; Kemertelidze, Nino (European Scientific Journal, ESJ, 2017)
Communication is a process of transmitting some information or data, ideas, thoughts, feelings, emotions through speech, writing, gestures, mimics, eyes and even nonverbal signals. In other words, communication is a process of establishing contacts and developing relations between people. The mostly widely spread types of communication is verbal and nonverbal. Namely this is the subject of research of the presented paper; though, it focuses on the subtype of nonverbal communication – visual communication. The papers deals with similarities and differences between these most important types of communication. The first and most vivid similarity between these types is that in both case we deal with the process of transferring and receiving the information. Secondly, both of them are connected with brain. In both cases, perceptual processing determines the type and amount of information that is sent to the brain for further thought. But if in verbal communication brain receives the information through the organs of hearing (by the uttered words), in the second case the process is accomplished through the organs of vision (by the viewed object). In both cases, the addressee should be very well aware of codes sent by the addresser; otherwise there will be no communication. But in case of verbal communication words, phrases and sentences should be properly understood and in case of visual communication – the objects, images should be properly perceived where symbolism should definitely be minded.